The impact of quality of life measured by WHOQOL-BREF on mortality in maintenance hemodialysis patients: a single center retrospective cross-sectional study - Seong Gyu Kim; In Hee Lee (Journal of Yeungnam Medical Science, 2023)
Background Several previous studies have reported that quality of life (QoL) in hemodialysis patients affects mortality. However, the 36-item Short Form Health Survey, which has been used mainly in previous studies, is complicated in terms of questionnaire composition and interpretation. This study aimed to identify the impact of QoL on mortality in hemodialysis patients using an easier and simpler diagnostic tool. Methods This retrospective study included 160 hemodialysis patients. QoL was evaluated using the World Health Organization Quality of Life Questionnaire-Brief version (WHOQOL-BREF). Psychosocial factors were evaluated using the Hospital Anxiety and Depression Scale, Multidimensional Scale of Perceived Social Support, Montreal Cognitive Assessment, and Pittsburgh Sleep Quality Index. We also evaluated medical factors, such as dialysis adequacy and laboratory results. Results The mean hemodialysis vintage was 70.7±38.0 months. The proportion of patients who were elderly was higher in the mortality group than in the surviving group, and the Charlson Comorbidity Index score was also higher in the former group. Of the four domains of the WHOQOL-BREF, the physical health and psychological scores of the mortality group were significantly lower than those of the survival group. When the score in the physical health domain or psychological domain was ≤10, the 10-year mortality rate after hemodialysis initiation increased by approximately 2.3- and 2-fold, respectively. Conclusion QoL may have a significant effect on mortality in patients undergoing hemodialysis. The WHOQOL-BREF is an instrument that can measure QoL relatively easily and can be used to improve the long-term prognosis of patients undergoing hemodialysis.